Development of Web-Based Uteach Tutoring Application - Rolly Lontaan; Stenly Ibrahim Adam; Oktoverano Lengkong; Virgil Steven Weol; Gerald Varon Alexius Poluan (CogITo Smart Journal, 2024)
In the rapidly evolving digital era, challenges in the field of education have become increasingly complex. This research aims to develop the UTeach learning guidance application, designed to assist students of Universitas Klabat in addressing academic issues. The application enables students to book mentors and meet face-to-face for guidance sessions. By implementing and utilizing the prototype model development method using the Software Development Life Cycle (SDLC), this study designs a prototype application aimed at facilitating student access to learning guidance by reducing time and distance barriers. Prototype testing is conducted through trials to evaluate the performance and usability of the application. This application is anticipated to serve as a potential tool in supporting Universitas Klabat students in improving academic performance and addressing financial issues. Development recommendations for this application may include adding conversation features, incorporating notification features, and developing a mobile application to enhance user efficiency. This research contributes to the advancement of educational technology by offering innovative solutions to enhance student learning experiences.